Which personal values matter most? Job performance and job satisfaction across job categories - Ismail, Hussein N. (2019)
Purpose As one of the first studies in this field, the purpose of this paper is to explore the effect of personal values on job performance and job satisfaction across different jobs. Further, it aims to identify personal value types that are positively, or negatively, related to behavioural and attitudinal outcomes in different job categories. Design/methodology/approach Based on a sample of 270 participants across several job categories including finance, accounting, marketing, sales, HR (human resources), operations and information technology (IT), this research explores the relationship between personal values, job performance and job satisfaction across the listed job categories. Ordinary least square (OLS) stepwise-regression and partial least square (PLS) regression were used in analysing the results. Findings Findings showed that for some of the jobs examined, different types of personal values were associated with different worker outcomes. Originality/value This research study identifies sets of personal values that are suited to some jobs more than others in terms of job performance and job satisfaction outcomes. Moreover, this research demonstrates the importance of controlling for job categories in future research models that investigate the links between values, performance and satisfaction.